2006
DOI: 10.1093/bja/ael097
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and liver microcirculation during autoregulation and haemorrhagic shock in rabbit model

Abstract: Background. Direct evidence of nitric oxide (NO) involvement in the regulation of hepatic microcirculation is not yet available under physiological conditions nor in haemorrhagic shock. Methods. A laser Doppler flowmetry was used to measure liver perfusion index and a specific NO-sensitive electrode was inserted into liver parenchyma of anaesthetized rabbits. Hepatic autoregulation during moderate hypovolaemia {mean arterial pressure at 50 mm Hg without liver perfusion alteration; blood withdrawal 17.7 (4.2) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Reduced glutathione is increased and nitric oxide levels decreased following the administration of antidepressant drugs. In the liver, nitric oxide is involved in regulation of hepatic haemodynamics (Mittal et al, 1994[ 46 ]; Lhuillier et al, 2006[ 41 ]) and in hepatic regeneration (Tuncyurek et al, 2006[ 67 ]). Studies indicated that inhibition of nitric oxide synthase increased hepatic lipid peroxidation, serum liver enzymes and bilirubin in CCl 4 -intoxicated rats (Muriel, 1998[ 51 ]), while increasing nitric oxide availability with L-arginine improved hepatic arterial and portal blood flow and sinusoidal oxygenation in experimental hepatic steatosis (Ijaz et al, 2005[ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced glutathione is increased and nitric oxide levels decreased following the administration of antidepressant drugs. In the liver, nitric oxide is involved in regulation of hepatic haemodynamics (Mittal et al, 1994[ 46 ]; Lhuillier et al, 2006[ 41 ]) and in hepatic regeneration (Tuncyurek et al, 2006[ 67 ]). Studies indicated that inhibition of nitric oxide synthase increased hepatic lipid peroxidation, serum liver enzymes and bilirubin in CCl 4 -intoxicated rats (Muriel, 1998[ 51 ]), while increasing nitric oxide availability with L-arginine improved hepatic arterial and portal blood flow and sinusoidal oxygenation in experimental hepatic steatosis (Ijaz et al, 2005[ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Girisgin et al 10 , using a experimental model in rabbits, studied importance of early and effective fluid resuscitation in hypovolemic shock treatment with the utilization of fluid replacement via the rectum, as a possible lifesaving method in situations where veins cannot be accessed quickly. Lhuillier et al 11 , also with a rabbit model, evaluate the nitric oxide involvement in the regulation of hepatic microcirculation under physiological conditions and in hemorrhagic shock, and concluded that it plays a important role in the autoregulation of liver microcirculation during the hemorrhagic shock. In the same manner, Komori et al 12 , studied the effects of hydroxyethyl starch on the microcirculation, hemodynamics, and colloidal osmotic pressure in a rabbit model of hemorrhagic shock, and verified that intravenous infusion of this solution effectively maintains these parameters during acute severe hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In liver sinusoids, specialized contractile endothelial cells exist which may be involved in the local control of haemodynamics and which are sensitive to vasoactive agents (Bani et al 2001). Nitric oxide is involved in the modulation of hepatic microcirculatory perfusion (Li et al 2003;Lhuillier et al 2006) and increasing hepatic bioavailability of nitric oxide has been shown to protect against experimental liver injury. In this context, in rats treated with CCl 4 , inhibition of nitric oxide synthase resulted in increased hepatic lipid peroxidation, serum liver enzymes and bilirubin (Muriel 1998), whereas the administration of L-arginine improved hepatic arterial and portal blood flow and sinusoidal oxygenation in experimental hepatic steatosis (Ijaz et al 2005).…”
Section: Discussionmentioning
confidence: 99%